Preferensi Konsumen Dalam Memilih Cafe Di Kota Malang Menggunakan Analisis Konjoin - Anggi Triutami; Pardiman Pardiman; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Cafe is a place to relax and can buy some foods and drinks that are identical to tables and chairs. This study aims to determine the order of consumer preferences regarding the combination of attributes and attribute levels in choosing a cafe in Malang City. This research was conducted on 96 respondents who visited or who had visited a cafe. This research method uses conjoint analysis with a sampling technique that is purposive sampling and the type of research is quantitative descriptive. There are six attributes used in this study, each with three attribute levels. The results of this study obtained the order of attribute combinations and attribute levels regarding consumer preferences in choosing cafes in Malang City, namely the price of Rp. 10,000-Rp. 15,000, location close to residence, outdoor cafe atmosphere, wifi facilities, responsive service, and products with menu sizes that match the price. Keywords: Consumer Preference, Cafe, Conjoint Analysis